The Effect of Cumin (Cuminum cyminum) Addition as Source of Essential Oils on Nutrien Digestibility, VFA, Amonia and Methan Production - Kurniawati, Asih (2017)
In vitro gas production technique was used to evaluate the effects of different doses of cumin (Cuminum cyminum) on rumen in vitro nutrient digestibility, VFA, ammonia and methane production. Addition of cumin correspond to essential oil levels of 0, 25, 50, 75 and 100 mg/L of fermentation medium, Fermentation was conducted according to Menke and Steingab methode for 24h. After 24 h, incubation was stopped and gas produced in each fermenter were collected to measured methane production, then fermentation broth was filtered to determine nutrient digestibility from the residual feed. Filtrate was used as sample for VFA and ammonia determination. Addition of cumin did not has detrimental effect on rumen fermentation. It did not alter pH, dry matter and organic matter digestibility, VFA and methane production. However ammonia concentration, crude protein and crude fiber digestibility were changed by cumin addition. Crude protein digestibility at cumin level 75 and 100 mg/L lower than control and cumin levels 25, 50 mg/L groups. Ammonia concentration reduced as effect of cumin addition. Crude fiber digestibility was higher at all level of cumin addition. In conclusion, cumin have capability to alter rumen fermentation and it has been potency to be used as additive.